A CONFISSÃO EM ACORDO DE NÃO PERSECUÇÃO PENAL E A IMPOSSIBILIDADE DE SUA UTILIZAÇÃO NA AÇÃO PENAL - Carvalho, Gabrielly Santos de; Santos, Helen Janine dos; Bleme, Hortˆência Maria; Santos, Marcos Vinícius Moreira dos; Santiago Neto, José de Assis (Sinapse Múltipla, 2020)